Posted by **Blah** on Thursday, February 28, 2013 at 11:31pm.

(x^n-1)/((x-1) )=(x-α^1 )×(1-α^2 )×………..(x-α^((n-1)) )

How do we prove that n = the multiplication of the second term using limits and l'hopital's rule.

## Answer this Question

## Related Questions

- Pure Mathematics - 4) The roots of the equation z^2+2z+4=0 are denoted by α...
- physics - In Physics, it is important to use mathemat- ical approximations. For ...
- math - Complex numbers α and β satisfy αα¯=ββ¯=&#...
- Calculus - Challenge question - Our teacher gave us this problem as a challenge...
- trig - Please help me! SHORT ANSWER. Write the word or phrase that best ...
- Math Trigonometry - Given w=2+2i and v=−5√3+5i, vw^2 can be ...
- Math - If α and β are two angles in Quadrant II such that tan α...
- Probability - Consider an RV X with the following density given parameters α...
- Quantum Physics - Let f:{0,1}->{0,1} with f(101)=1 and f(x)=0 for x ≠ ...
- Trigonometry - Verify the identity algebraically. This problem is very ...